2019
DOI: 10.1021/acs.joc.9b01375
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed C(2)–H Arylation of Indoles with Aryl Chlorides under Neat Conditions

Abstract: Nickel-catalyzed regioselective C(2)–H arylation of indoles and pyrroles with aryl chlorides is achieved under neat conditions. This method allows the efficient coupling of diverse aryl chlorides employing a user-friendly and inexpensive Ni­(OAc)2/dppf catalyst system at 80 °C. Numerous functionalities, such as halides, alkyl ether, fluoro-alkyl ether, and thioether, and substituted amines, including heteroarenes like benzothiazolyl, pyrrolyl, indolyl, and carbazolyl, are well tolerated under the reaction cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 56 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…The halide functionalities −F, −Cl and −CF 3 were well tolerated at the para position of arene and afforded the arylated products in low to moderate yields ( 3 ak – 3 am ). Notably, the −CF 3 containing aryl electrophile was unreactive under the nickel‐catalysis that was demonstrated earlier . The 1,3‐dioxolane derivative, 2 n could be employed in the arylation reaction providing 84% of the coupled product 3 an .…”
Section: Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…The halide functionalities −F, −Cl and −CF 3 were well tolerated at the para position of arene and afforded the arylated products in low to moderate yields ( 3 ak – 3 am ). Notably, the −CF 3 containing aryl electrophile was unreactive under the nickel‐catalysis that was demonstrated earlier . The 1,3‐dioxolane derivative, 2 n could be employed in the arylation reaction providing 84% of the coupled product 3 an .…”
Section: Methodsmentioning
confidence: 83%
“…Interestingly, the aryl iodides containing substituted amine and N ‐heterocycles, like N ‐pyrrolyl, N ‐indolyl, N ‐carbazolyl groups reacted efficiently and afforded the desired arylated products in excellent yields. Such functionalities containing aryls have shown moderate reactivity under the nickel catalysis . Unfortunately, the current method failed to tolerate the base sensitive functionalities, such as acetyl, ester, amides and nitro groups.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Notably, the reaction proceeded in the absence of solvent using a strong base LiHMDS, which made this reaction more environmentally friendly. Later on, the same group came up with a new catalyst system, Ni/dppf, which could couple high‐demand and challenging aryl chlorides with indoles and pyrroles to produce C‐2 arylated indoles and pyrroles . Notably, these reactions were performed at 80 °C and demonstrated to be very useful for the tolerance of diverse functionalities like halides, alkyl ether, fluoroalkyl ether, thioether, and substituted amines, including benzothiazolyl, pyrrolyl, indolyl, and carbazolyl groups.…”
Section: Arylation Reactionsmentioning
confidence: 99%
“…Later on, the same group came up with a new catalyst system, Ni/ dppf, which could couple high-demand and challenging aryl chlorides with indoles and pyrroles to produce C-2 arylated indoles and pyrroles. [20] Notably, these reactions were performed at 80°C and demonstrated to be very useful for the tolerance of diverse functionalities like halides, alkyl ether, fluoroalkyl ether, thioether, and substituted amines, including benzothiazolyl, pyrrolyl, indolyl, and carbazolyl groups. The preliminary mechanistic study suggested that the reaction proceeds via a single electron transfer (SET) pathway involving the aryl radical.…”
Section: Ni-catalyzed Reactionsmentioning
confidence: 99%